2014
DOI: 10.1021/bi5008172
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Apolipoprotein E to Oligomers and Fibrils of Amyloid-β Alters the Kinetics of Amyloid Aggregation

Abstract: Deposition of amyloid-β (Aβ) in Alzheimer’s disease (AD) is strongly correlated with the APOE genotype. However, the role of apolipoprotein E (apoE) in Aβ aggregation has remained unclear. Here we have used different apoE preparations, such as recombinant protein or protein isolated from cultured astrocytes, to examine the effect of apoE on the aggregation of both Aβ1–40 and Aβ1–42. The kinetics of aggregation, measured by the loss of fluorescence of tetramethylrhodamine-labeled Aβ, is shown to be dramatically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
100
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 55 publications
14
100
0
1
Order By: Relevance
“…On the contrary, other studies suggest that apoE isoforms can also inhibit A aggregation, with apoE4 being least effective (63)(64)(65)(66). These seemingly contradicting findings may be explained by the variable experimental conditions, such as the species and source of A used (67) (A40 versus A42, recombinant versus synthetic) and, especially, the preparation and the (resulting) lipidation state of apoE.…”
Section: Apoe and A Aggregationmentioning
confidence: 97%
“…On the contrary, other studies suggest that apoE isoforms can also inhibit A aggregation, with apoE4 being least effective (63)(64)(65)(66). These seemingly contradicting findings may be explained by the variable experimental conditions, such as the species and source of A used (67) (A40 versus A42, recombinant versus synthetic) and, especially, the preparation and the (resulting) lipidation state of apoE.…”
Section: Apoe and A Aggregationmentioning
confidence: 97%
“…Fig. 4A shows that according to concentration-based LSPR the shift increased from 5 nM to 9 nM and was saturated from 10 nM to 20 nM, which indicated that higher ApoE4 concentration inhibits the growth kinetics of fibrils via a mediation of the interaction between ApoE4 and Aβ fibrils and then stabilization of fibrils (Garai et al, 2014).…”
Section: Detection Limit Of the Biosensormentioning
confidence: 95%
“…As summarized in the introductory paragraphs, the physiological functions of the apoE molecule involve various binding events that are mediated by amphipathic α-helices located in the N-and C-terminal domains. After dissociation of apoE tetramers [such as occur in plasma HDL-LpE (35)] to the monomeric state (15,47), the C-terminal helical domain initiates hydrophobic interactions such as binding to lipid and lipoprotein surfaces (7,44), and to amyloid-β (13,48). The present HX results prove that the amphipathic α-helix organization in the C-terminal domains of tetrameric WT apoE3 and apoE4 is different and suggest the following explanation for the molecular basis of the enhanced binding of apoE4 in such situations.…”
Section: Influence Of Differences In Secondary Structure On Apoe3 Andmentioning
confidence: 99%
“…Therefore, at the same apoE expression level, progression down the lipolysis cascade will be relatively limited (8), leading to higher plasma cholesterol levels and, potentially, the increased incidence of cardiovascular disease associated with apoE4 (6). Second, in the brain, the enhanced binding of apoE4 to amyloid-β oligomers can alter the kinetics of aggregation by inhibiting growth and nucleation on the pathway to forming fibrils (13). This effect may promote pathogenesis by, for example, leading to greater accumulation of the cytotoxic oligomeric forms of amyloid-β.…”
Section: Influence Of Differences In Secondary Structure On Apoe3 Andmentioning
confidence: 99%
See 1 more Smart Citation